2018
DOI: 10.2147/ott.s169947
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone inhibits proliferation, migration and invasion of HUUA cells and promotes its apoptosis by regulation of FAK and PI3K/AKT signaling pathway

Abstract: PurposeThe aim was to investigate mifepristone effects on endometrial carcinoma and the related mechanism.MethodsHHUA cells were treated with DMEM containing different concentrations of mifepristone. HHUA cells treated with 100 μmol/L mifepristone were named the Mifepristone group. HHUA cells co-transfected with pcDNA3.1-PI3K and pcDNA3.1-AKT overexpression vectors were treated with 100 μmol/L mifepristone and named the Mifepristone + PI3K/AKT group. mRNA expression was detected by quantitative reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Aimin et al, showed that mifepristone at 10 μM and 100 μM concentrations reduced the proliferation of type I endometrial cancer Ishikawa cells 11 . A similar study showed that 50 to 100 μM mifepristone reduced the proliferation and wound healing rate of HUUA endometrial cancer cells 12 . However, the concentrations used in these studies were very high and cannot be used to predict the effect in human cancer tissue.…”
Section: Discussionmentioning
confidence: 73%
“…Aimin et al, showed that mifepristone at 10 μM and 100 μM concentrations reduced the proliferation of type I endometrial cancer Ishikawa cells 11 . A similar study showed that 50 to 100 μM mifepristone reduced the proliferation and wound healing rate of HUUA endometrial cancer cells 12 . However, the concentrations used in these studies were very high and cannot be used to predict the effect in human cancer tissue.…”
Section: Discussionmentioning
confidence: 73%
“…In this study, the TUNEL assay showed that mifepristone induced apoptosis in endometrial cells, which is consistent with previous studies. [ 48 ] Immunofluorescence detection of caspase‐1 showed that mifepristone induced pyroptosis in endometrial cells. Further experiments revealed that GSDMD, cleaved caspase‐1, NLRP3, and IL‐1β expression levels were significantly elevated in mifepristone‐induced failure of implantation mice.…”
Section: Discussionmentioning
confidence: 99%
“…MF was capable of diminishing cell migration through the 8 μm pore polycarbonate membrane as early as 6 h in each cell line studied. Supporting our data with ovarian, breast, glial, and prostate cancer cell lines, it was reported very recently that MF inhibited migration induced by progesterone in human astrocytoma cells [38], that both MF and its metabolite metapristone inhibited the chemotactic migration and mobility in SKOV-3 and IGROV-1 ovarian cancer cell lines facilitated by activation of the chemokine SDF-1/CXCR4 [29, 39], and that MF inhibited migration and invasion of endometrial carcinoma cells [40].…”
Section: Discussionmentioning
confidence: 99%